(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Computer will never replace teacher but the effective use of computers enhance the desired learning. Technology is a must to reach international standards in education. As said by our finance minister P. Chidambaram, we are 30 years behind in technology when compared to the developed countries. This will affect the growth of the nation. We are now happy that we launched the EDUSAT in the orbit on September 20, 2004. This is not the end. But there is a long way to go before reaching excellence in the international scenario. Let us strive for creating high-tech classrooms to make our children have global outlook.Present study favors that computer technology application in special education can accelerate the appropriate development of exceptional children. By using appropriate software programme the special educators can handle these children in a proper way. Children can learn with their own capacity and speed. The computer technology can be helpful in implementing individualized education programme for students with disabilities. The teacher and student both can make self-evaluation and determine the goal achievement. Future technological advances can enable the educators to analyze and track the impaired student’s development much greater precision than is now possible and to use this information in plan appropriate instruction for the impaired students and to use this information in planning appropriate instruction for special needy children.